2005
DOI: 10.1258/002221505774783485
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency vs laser in the management of mild to moderate obstructive sleep apnoea: does the number of treatment sessions matter?

Abstract: In OSA, fewer treatment sessions are needed with LAUP (one session) than with BRVTR (three sessions) to achieve a favourable outcome. In LAUP more treatment sessions (two) are needed to maintain a longer-term favourable outcome than those needed to achieve short-term favourable outcome (one session), which is not the case with BRVTR (three sessions are needed to achieve both short- and long-term favourable results).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 19 publications
(32 reference statements)
1
14
0
Order By: Relevance
“…The CPAP studies included trials comparing CPAP versus sub-therapeutic (sham) CPAP [ 4 34 ], CPAP versus an oral placebo [ 33 , 35 43 ], CPAP versus conservative or no therapy [ 10 , 22 , 44 54 ], CPAP versus an oral appliance [ 4 , 5 , 36 , 51 , 55 63 ], CPAP versus postural therapy [ 64 67 ], and CPAP alone assessing different means to modify adherence (e.g., with vs. without a humidifying element) [ 8 , 21 , 30 , 68 79 ]. The surgical trials assessed a variety of single- and multi-stage procedures incorporating uvuloplasty [ 22 , 80 117 ], mandibular advancement [ 118 , 119 ], laser treatments [ 120 125 ], radiofrequency tissue reduction and other lingual procedures [ 117 , 125 134 ], and palate implants [ 135 141 ], in addition to five trials specifically evaluating the safety versus risks of OSA surgery, including its safety as an outpatient/same-day procedure [ 142 146 ]. The PRISMA charts seen in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The CPAP studies included trials comparing CPAP versus sub-therapeutic (sham) CPAP [ 4 34 ], CPAP versus an oral placebo [ 33 , 35 43 ], CPAP versus conservative or no therapy [ 10 , 22 , 44 54 ], CPAP versus an oral appliance [ 4 , 5 , 36 , 51 , 55 63 ], CPAP versus postural therapy [ 64 67 ], and CPAP alone assessing different means to modify adherence (e.g., with vs. without a humidifying element) [ 8 , 21 , 30 , 68 79 ]. The surgical trials assessed a variety of single- and multi-stage procedures incorporating uvuloplasty [ 22 , 80 117 ], mandibular advancement [ 118 , 119 ], laser treatments [ 120 125 ], radiofrequency tissue reduction and other lingual procedures [ 117 , 125 134 ], and palate implants [ 135 141 ], in addition to five trials specifically evaluating the safety versus risks of OSA surgery, including its safety as an outpatient/same-day procedure [ 142 146 ]. The PRISMA charts seen in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Atef et al [39], there was a mean reduction of AHI from 26.3 to 16.6 after 18 months in the RF-UPP group (n = 64). Seventy-five patients that were treated with a standard LAUP were used as control.…”
Section: Rf-uppmentioning
confidence: 87%
“…Atef et al compared the use of radiofrequency versus laser-assisted uvulopalatoplasty for obstructive sleep apnoea. They concluded that both treatments required multiple treatments, but radiofrequency appeared to have a more sustained long-term outcome [20]. Back et al reviewed the use of radiofrequency in snoring surgery and identified that the symptoms of snoring were reduced in the short-term, but long-term data was lacking [13].…”
Section: Soft Palatementioning
confidence: 99%